Kompetensi Guru PAI Bersertifikasi Terhadap Penerapan Kurikulum PAI pada Sekolah Dasar di Kecamatan Sultan Daulat Kota Subulussalam - Agustari Husni; Warul Walidin; Masbur Masbur (Tadabbur: Jurnal Peradaban Islam, 2023)
This study aimed to investigate the level of competence of certified Islamic religious education teachers in implementing the Islamic religious education curriculum, to describe the challenges and opportunities encountered by certified Islamic religious education teachers in implementing the Islamic religious education curriculum, and to explore the form of the implementation of the Islamic religious education curriculum in elementary schools in Sultan Daulat Sub-district, Subulussalam City. This study used a qualitative descriptive research method, collecting data by means of interview, observation, and documentation. Data analysis consisted of data reduction, data display, and conclusion or verification. The findings of this study showed that certified teachers of Islamic religious education possessed a number of competencies in implementing the Islamic religious education curriculum. The competencies included competence in planning and carrying out the learning process, competence in managing the learning process, intellectual competence, social competence, and personality competence. Further, in general, the opportunity experienced was teaching Islamic religious lessons directly by certified teachers of Islamic religious education. The challenges faced by the teachers were the low level of student motivation in Islamic religious education lessons and the inadequate infrastructure that supported learning Islamic religious education.